PENGARUH STRATEGI PEMBELAJARAN DAN MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR MEMBUAT POLA KEBAYA MODIFIKASI SISWA SMK NEGERI 10 MEDAN - Ermidawati Ermidawati (Universitas Negeri Medan, 2015)
ABSTRACT This study aims to determine : (1) the comparison between learning process on making modification of students’ kebaya model who are tought with the contextual learning strategy and the result of study in making the modification of students’ kebaya model; (2) the differences of result in making modification of kebaya model who has the high learning motivation with the student who has low learning motivation; and (3) the interaction between learning strategy and the learning motivation to the result of study in making student’s modification kebaya model. This reasearch was done in SMK Negeri 10 Medan in odd semester 2014/2015. The populations were 104 people as the whole students in grade XI, the samples were grade XI Tata Busana-2 were 35 people and grade XI Tata Busana-3 were 34 people. The instruments were used to collect the data were the result of learning test and form of learning motivation. The research method was Quasi Experimental method with the research factorial design 2 x 2. The data analysis used ANAVA on significant a = 0,05. The result of research data analysis shows that : (1) the result of learning in making modification in students’ kebaya model who are taught by the contextual learning strategy is higher than the result of students who are taught by using Expository Learning Strategy (Fcalculated= 4,265 > Ftable = 4,07), (2) there is a significant differences between the learning result of students who have high learning motivation with the students who have low learning motivation, (Fcalculated; = 94,33. > Ftable=4,07 ), dan 3) there is interaction between the learning strategy and the learning motivation to the result of learning process in making students’ modification kebaya (Fcalculated= 4.741 > Ftable =4,07). Kata Kunci : Strategi pembelajaran, hasil belajar dan motivasi berprestasi.